Release of Nitrocatecholsulfatase during Blood Coagulation from Thrombocytes - Polášek, J; Rotrekl, B (Thrombosis and Haemostasis, 1968)
In this study the release of NCS from blood platelets into the serum during blood coagulation and its dependence on time and temperature have been studied. In a group of 10 males and 10 females, the NCS activity in the plasma was determined and compared with that in the serum.